PKM. KOMUNITAS BELAJAR GURU MATEMATIKA KABUPATEN BADUNG DALAM PELATIHAN PEMANFAATAN PLATFOM MERDEKA MENGAJAR - I Wayan Sumandya; Ni Luh Made Manik Widayani; I Nyoman Bagus Suweta Nugraha (LPPM Universitas PGRI Mahadewa Indonesia, 2022)
The independent curriculum is a new breakthrough from the Ministry of Education and Culture. Along with the launch of the independent curriculum, the Ministry of Education and Culture also launched an independent teaching platform. The Merdeka Teaching Platform is a platform that contains various benefits in carrying out learning. Welcoming the new 2022/2023 academic year simultaneously high school schools in Badung Regency are implementing the Merdeka Curriculum, where training on the complete independent curriculum is available on the independent teaching platform. The math teacher learning community is a place for high school mathematics teachers in Badung Regency to learn and share good practices. However, this community has not gained much knowledge about the Merdeka Mengajar Platform. On July 6, 2022, training was held on using the independent teaching platform. The steps for implementing the training are divided into several sections as follows: Planning, Implementation of the Workshop, Training on practicing the Merdeka Teaching Platform. The output targets of this training are (1) mathematics teachers at SMAN Badung district know the contents of the independent teaching platform; (2) teachers can take advantage of the independent teaching platform as a means for independent training; and (3) teachers can share good practices related to learning that has been carried out.